A regime shift in intertidal assemblages triggered by loss of algal canopies: A multidecadal survey. (September 2020) - Álvarez-Losada, Óscar; Arrontes, Julio; Martínez, Brezo; Fernández, Consolación; Viejo, Rosa M.
Abstract: Canopy-forming macroalgae recently experienced a worldwide decline. This is relevant, because canopies sustain complex food webs in temperate coasts. We assessed the die-back of the canopy-forming alga Fucus serratus in N Spain, at its warm distributional range boundary, and its effects on associated assemblages. We combined long-term descriptive surveys with canopy-removal experiments. Results showed that rapid shifts to turf-forming communities were mostly the direct consequence of the canopy loss, rather than a concurrent process directly triggered by climate change. The switch alters the whole food web, as the prominent role of F.serratus and other cold-temperate intertidal fucoids is not being replaced by functionally equivalent species. Canopy loss caused a rapid biotic homogenization at regional scale which is spreading towards the west, from the edge to the central part of the former distributional range of F.serratus in N Spain. The most obvious effect is the ecological and functional impoverishment of the coastal system. Highlights: The canopy alga Fucus serratus experiences a continuous westward retreat in N Spain. The decline is related to rising physical stresses and increased grazing by fishes. Regime shifts were examined by combining experiments and long-term surveys. Canopy loss directly caused a biotic homogenization in assemblages at regional scale. The spread of canopy loss reduces productivity and alters coastal food webs.